Pengembangan Blueprint Sistem Informasi Akademik Terintegrasi (Studi Kasus : IAIN Syekh Nurjati Cirebon) - Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2016)
The information system is used to present information for management decision making and running the activities involved in an organization. Blue Print of information technology essentially provides college's strategic plan to implement and build information systems in college which is a derivative of the Business Plan colleges where individual companies generally have a strategic plan. This study aims to create an enterprise architecture for IAIN Syekh Nurjati Cirebon, in the form of IT blueprint that could later be used by the enterprise to achieve its vision and mission. The planning is done by utilizing EAP methodology (Enterprise Architecture Planning). The means used is through the process of defining the enterprise architecture in the form of data architecture, application architecture, technology architecture, business architecture, as well as integration architecture. Once the rest of the enterprise architecture is defined, the result made implementation plan is a plan for the implementation of enterprise architectures in the future as a blueprint for the information technology IAIN Sheikh Nurjati Cirebon.